2020
DOI: 10.1038/s41428-020-00396-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of poly(3-hydroxyalkanoate) and poly(ε-caprolactone) via biological carbon cycles in marine environments

Abstract: Approximately 4.8–12.7 million tons of plastic waste has been estimated to be discharged into marine environments annually by wind and river currents. The Ellen MacArthur Foundation warns that the total weight of plastic waste in the oceans will exceed the total weight of fish in 2050 if the environmental runoff of plastic continues at the current rate. Hence, biodegradable plastics are attracting attention as a solution to the problems caused by plastic waste. Among biodegradable plastics, polyhydroxyalkanoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(102 citation statements)
references
References 159 publications
1
101
0
Order By: Relevance
“…However, factors that influence the degradation of composites and bioplastics are necessary. Some of the marine microorganisms that are known to degrade PHAs [94] As in polysaccharide-based bioplastics, crystallinity in polyester bioplastics from microbial synthesis plays an important role in the biodegradation process. In bioplastics with higher proportions of amorphous regions, depolymerization occurs more quickly through abiotic or biotic action.…”
Section: Biodegradation Of Microbe-based Polymers Bioplasticsmentioning
confidence: 99%
“…However, factors that influence the degradation of composites and bioplastics are necessary. Some of the marine microorganisms that are known to degrade PHAs [94] As in polysaccharide-based bioplastics, crystallinity in polyester bioplastics from microbial synthesis plays an important role in the biodegradation process. In bioplastics with higher proportions of amorphous regions, depolymerization occurs more quickly through abiotic or biotic action.…”
Section: Biodegradation Of Microbe-based Polymers Bioplasticsmentioning
confidence: 99%
“…For example, strips of PHBV with a thickness of 1 mm showed a total mass loss of 100% after 70 days at 20-24 • C in industrial composting facilities; a complete degradation via composting can be observed for PCL within a few weeks. Figures on biodegradation of PHA and PHB can be found in another review [13] and the biodegradability in marine environment of PHA and PCL has been extensively discussed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Depolymerases catalyze hydrolysis, thus producing free D(−)-3-hydroxybutyrate, which is then oxidized to acetoacetate by a NAD-specific dehydrogenase. Degradation of PHA can be realized in various environments such as soil, fresh water, and marine environments [37,38]. Some of the most dominant PHA-degrading microorganisms belong to the bacterial genera of Bacillus, Ralstonia, Pseudomonas, Alcaligenes, Mycobacterium, Comamonas, Acinetobacter, Azospirillum, and Streptomyces [37,39,40].…”
Section: Introductionmentioning
confidence: 99%